Efektivitas Komunikasi Partisipatif dalam Pelaksanaan Prima Tani di Kecamatan Sungai Kakap Kabupaten Pontianak, Kalimantan Barat - P.G. Cahyanto; B.G. Sugihen; Hadiyanto . (Institut Pertanian Bogor, 2008)
The objectives of this research are to know the participatory communication effectiveness in the implementation ofintegrated farming model and to analyze the relationship between individual characteristic of farmer withparticipatory communication in implementation of Prima Tani. The research was designed asa survey on thecharacter of descriptive correlation. Sample chosen by simple random sampling method consisting of 100 farmers orpeasants from 10 groups of peasants that participate in Prima Tani Progam. The collected data is analyzed usingnon-parametric statistics procedure, in this case Rank Spearman and Chi Square. The result of the study indicate that(1) Age correlate significantly with planning, Non formal education correlates significantly with inspiring idea,planning and implementation, Motivation correlate significantly with inspiring idea, Income level correlatesignificantly with planning, implementation and assessment, Membership period correlate significantly with inspiringidea and implementation. Inspiring idea correlate with attitude and knowledge in integrated farming model orprogram. Implementation program correlate with attitude and knowledge, and negatitivity correlates with behaviorchange. The assessment program correlate with significantly with attitude and knowledge. Farmer attitude andknowledge in this model are not always in line with behavior change that would expected.